Comparative 3E Analysis of Semi-Cylindrical Solar Still and Double-Slope Solar Still - Kshitij Yugbodh; Rahul Agrawal; Ekta Jain; Kennedy S. (International Journal of Energy and Thermal Applications, 2024)
Potable clean water is the prime requirement for the human being. There is an urgent requirement to shift to the non-conventional method of water desalination. Solar desalination is one of the economical methods that has no adverse effect on the environment due to environmental constraints and climate change. Experiments have been performed to find out the performance of SCSS (semi-cylindrical solar still with iron wick) and DSSS (double-slope solar still with jute wick). The experimental results show good hourly and cumulative productivity of the Stills. The cumulative yield of SCSS is 44.35% more than DSSS. The maximum energy and exergy efficiency received for SCSS are 47.92% and 18.28% respectively. The cost per litre (CPL) of SCSS is also low which is 0.88 Rs./lt.
Keywords: Solar still; desalination process; economic analysis; energy; exergy